Peningkatan Proses Pembelajaran Tematik Terpadu Menggunakan Model Discovery Learning pada Siswa Kelas V SD - Putri, Elisa Deka; Ahmad, Syafri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This research is motivated by integrated thematic learning that has not been well implemented, is still in the process of improving. This causes the integrated thematic learning process to be carried out to the maximum. The purpose of this study, to improve the integrated thematic learning process using the Discovery Learning model. This type of research is classroom action research using qualitative and quantitative approaches. This research was conducted in the second semester of the 2018/2019 academic year. The results of the study showed an increase in: (1) the learning plan, namely cycle I obtained a percentage of  83.33% (Good), cycle II obtained a percentage of 97.2% (Very Good). (2) the implementation of learning cycle I obtained a percentage of 79,7% , cycle II obtained a percentage of 96,9% (Very Good). It can be concluded that the Discovery Learning model can improve the integrated thematic learning process in elementary schools.